1998
DOI: 10.1097/00005537-199806000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Unilateral Submandibular Gland Excision on Salivary Flow in Noncancer Patients

Abstract: Unilateral submandibular gland excision results in a decreased rate of resting salivary flow and an increase in subjective xerostomia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
63
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 8 publications
3
63
0
2
Order By: Relevance
“…Comparing the 2 groups that had a resection,, the difference was significant only for stimulated saliva. The result concerning the comparison between the group who had a unilateral submandibular gland excision (10 patients) and the control group (13 patients) was also supported by Cunning et al 17 On the pharmaceutical side, if there is residual salivary function, sialagogues, such as pilocarpine hydrochloride, a cholinergic antagonist, have also been mentioned to maximize the residual gland function by inducing vasodilatation in the salivary glands via stimulating a secretion with similar composition like in normal gland function.…”
Section: Discussionmentioning
confidence: 64%
“…Comparing the 2 groups that had a resection,, the difference was significant only for stimulated saliva. The result concerning the comparison between the group who had a unilateral submandibular gland excision (10 patients) and the control group (13 patients) was also supported by Cunning et al 17 On the pharmaceutical side, if there is residual salivary function, sialagogues, such as pilocarpine hydrochloride, a cholinergic antagonist, have also been mentioned to maximize the residual gland function by inducing vasodilatation in the salivary glands via stimulating a secretion with similar composition like in normal gland function.…”
Section: Discussionmentioning
confidence: 64%
“…Submandibular sialadenectomy successfully relieves symptoms 1,17 , but results in scarring and transient or permanent facial nerve weakness in up to 30% and 7% of cases, respectively 1,[8][9][10] . Unilateral submandibular gland excision halves the rate of resting salivary flow 3,8,17 . In keeping with the overall trend in surgery towards minimally invasive procedures, new techniques have been developed to preserve the gland whilst removing the obstruction.…”
mentioning
confidence: 99%
“…In addition, even in the cases determined to require the excision of submandibular gland because chronic inflammation and atrophy of the submandibular gland were suspected to be caused by the stones, in postsurgical histopathological findings, the cases with normal or almost normal excised submandibular gland tissues reached 57% [7]. According to reported studies, in the patients underwent the transoral removal of submandibular stones, function of the submandibular gland was assessed by scintigraph, and it was found that after the removal of stones, 75% submandibular glands recovered normal functions [8,9]. Therefore, numerous attempts have been made to preserve the submandibular gland.…”
Section: Discussionmentioning
confidence: 99%